Active methodologies as a space for knowledge management: an experience in higher education in Communication - Guaraldo, Tamara de Souza Brandão [UNESP] (Universidade Federal do Paraná, 2022)
Introduction: In the current scenario of higher education in the area of Communication, it is necessary to have an education that expands the capacity to meet the demands of the market. There is a growing need to combine theory and practice in teaching, and with that, the understanding of teamwork and the knowledge of the dynamics of the performance of communication agencies. The objective of this study is to understand how the use of active methodologies can create spaces for knowledge management and thus contribute to the learning of the profession in the disciplinary context in Communication courses. Method: Develops a descriptive qualitative research applied in classes in which the author taught in undergraduate courses in the area of Communication with the use of Project-based Learning methodology and the model of Five phase of the knowledge creation process. In the classroom, a dynamic of formation of communication agencies by groups of undergraduate students was applied in the period from 2014 to 2019. Results: The change from the traditional method to the proposed knowledge management process generated insecurity and an effort of interlocution by the students, demanding maturity, and a position of greater autonomy. The communication agencies set up by the students presented their identity and the communication pieces created, providing opportunities to get in touch with the job market. Conclusions: The knowledge management process materialized as soon as the interactions promoted reflections about the “I” itself, and it was possible to realize that knowledge management is a teaching-learning relationship and coexistence between all the actors in the teaching process.
Metodologias ativas como espaço de gestão do conhecimento: uma experiência no ensino superior em Comunicação
Keywords: Communication agencies; Communication. Project-Based Learning; Higher education; Knowledge management